Kelarutan Fosfat dan Ferro pada Tanah Sulfat Masam yang Diberi Bahan Organik Jerami Padi - Fahmi, Arifin; Radjagukguk, Bostang; Purwanto, Benito Heru (JOURNAL OF TROPICAL SOILS, 2009)
Phosphate and Ferrous Solubilty on Acid Sulphate Soils Treated with Rice Straw (A. Fahmi, B. Radjagukguk, and B. H. Purwanto): The objective of this research was to investigate the effect of application of organic matter from rice straw (RS) on phosphate and Fe2+  solubility in the acid sulphate soils.  The research was conducted in the glass house consisting of the three treatment factors using the completely randomized design with three replication.  The first factor was soil condition : continuous application of  RS and without application of RS during the last 5 years.  The second factor was fresh application of RS ; with application and without application, whereas the third factor was phosphate application consisting 3 rates of SP – 36 fertilizers (0.5; 1,0 and 1.5 of application dossage). The result showed the three factors interaction had a significant influence on soil pH at 2 weeks after planting, whilst   interaction between RS application and soil condition had a significant influence on soil pH, available phosphate at 4, 6 and 8 weeks after planting.  The interaction between RS application and phosphate fertilizers rate had a significant influence on soil pH 4 weeks after planting, and on available phosphate at 8 weeks after planting.  The main effect of RS application was significant on exchangeable Fe and soil pH at all observations periods.